The Growth of Calophyllum Inophyllum Scions Taken from Provenance Seed Stand in Wonogiri, Central Java - Hamdan , Hamdan Adma Adinugraha; Erytrina , Erytrina Windyarini; Trie , Trie Maria Hasnah; Arif , Arif Priyanto; Hendra, Hendra Firdaus; Budi , Budi Leksono (Jurnal Wasian, 2021)
Calophyllum inophyllum L. is one of species that has been identified as a source of oil suitable for biofuel, cosmetics and medicine. Until now, the propagation of this species uses generative methods. In the forest tree breeding program, after a plus tree is selected a vegetative propagation technique must be developed to maintain the genetic potential of the parent tree. This study was conducted to determine the growth response of selected clones in Provenance Seed Stand of C. inophyllum in Wonogiri, Central Java propagated using the grafting method. The research used was arranged in Randomized Completely Design with 22 clones as the parent tree treatments. Each treatment consisted of 5 grafted seedlings and repeated in 4 times. The results showed that the survival percentage of grafted seedlings ranges from 15 – 100 % at 2 months of age, which showed a fairly high variation among the selected clones. Increasing the success of the grafting technique on the C. inophyllum clones still needs to be done so that it can provide vegetative material for clone testing and operational planting. It is important to be conducted in order to produce C. inophyllum stands with high fruit productivity and oil yield.